Church planting : the man, the message, the mission - Patrick, Darrin, 1970-2020. (Wheaton, Ill. : Crossway, 2010)
The most critical human component of every church plant is the planter. Darrin Patrick, vice president of the Acts 29 Church Planting Network, looks at what Scripture teaches about this man's character, his teaching, and the aim of his church. Offering guidance and wisdom from years of experience, Patrick reminds us that ultimately no church will succeed apart from a man with a message who leads a church on a mission. --from publisher description
Why focus on men? -- A rescued man -- A called man -- A qualified man -- A dependent man -- A skilled man -- A shepherding man -- A determined man -- A historical message -- Salvation-accomplishing -- Christ-centered -- Sin-exposing -- Idol-shattering -- The heart of mission : compassion -- The house of mission : the church -- The how of mission : contextualization -- The hands of mission : care -- The hope of mission : city transformation.
Includes index.
Keywords: Church development, New; Evangelistic work; Missions -- Theory